BEHAVIOURAL CHARACTERISTICS OF OVERPARENTED CHILDREN AND THEIR PARENTS - Lijana Navickienė; Ilona Kupčikienė (Mokslo Taikomieji Tyrimai Lietuvos Kolegijose)
Parenting styles and behaviours are critical in shaping a child’s personality, beliefs, values, and behaviours, affecting their academic achievement, mental health, and future success. Being active in a child’s life can increase the child’s confidence, build a closer bond between parent and child, and increase the child’s chances of becoming a successful adult. However, excessive involvement and control over a child’s life can lead to negative consequences for the child’s development. Overparenting refers to overprotective and controlling behaviour towards the child when the parents tend to micromanage their child’s lives, make decisions for them, and shield them from challenges and disappointments. The study aims to reveal the behavioural characteristics of overparented children and their parents. 262 teachers across six countries (Slovenia, Portugal, Romania, Turkey, and Lithuania) participated in the study. An online survey using closed and open-ended questions was used to collect the data. The study results revealed that overparenting can negatively affect a child’s development, leading to dependence, poor decision-making skills, anxiety, reduced academic performance, and lack of resilience. Overparenting parents tend to micromanage their children’s lives, shield them from disappointment, and have unrealistic expectations. They may also lack trust in teachers, leading to strained relationships. Survey results suggest a lack of positive parenting skills and understanding of child development. To promote healthy parenting, it is crucial for parents to develop emotional regulation skills, positive parenting skills, and knowledge of their child’s social and emotional needs.